HUMANISME TEISTIK EMHA AINUN NADJIB DAN KONTRIBUSINYA BAGI KEHIDUPAN SOSIAL - Sumasno Hadi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2017)
Emha Ainun Najib, or Emha, is a poet, artist, writer, thinker, and other populist designations that exist in Indonesian society. As a writer, his essays in the 1980s to the 1990s very coloring various mass media in Indonesia. There, many critical discourses and sharp in highlighting the social reality, religion, art and culture. The studies reviewed Emha thoughts in perspective philosophy of humanism. The result was found, that the thought Emha have a strong spirit in his defense to the humanitarian aspects (humanism). Spirit is supported by the value of spirituality and religiosity that leads to ethical purpose, namely a quality of “consciousness”. Humanism Emha is theistic humanism which has the potential to be used as a solution-critical reflections on the problems of social life.